Measurement properties of the Haem‐A‐QoL in haemophilia clinical trials. Issue 3 (27th December 2016) - von Mackensen, S.; Eldar‐Lissai, A.; Auguste, P.; Krishnan, S.; von Maltzahn, R.; Yu, R.; Wyrwich, K. W.
Abstract : Introduction: Patients with haemophilia on long‐acting prophylactic treatment may experience an improvement in health‐related quality of life (HRQoL) through reductions in breakthrough bleeds and associated complications, including long‐term joint damage, compared with episodic treatment. Aim: This analysis examined clinical trial data to understand the psychometric characteristics (reliability, validity and sensitivity to change over time) of the Haem‐A‐QoL Questionnaire in adult males with haemophilia. Methods: Two recent, multinational, Phase 3 clinical trials of new, long‐acting factor concentrates (A‐LONG: rFVIIIFc; B‐LONG: rFIXFc) assessed HRQoL in adolescent and adult males with severe haemophilia A or B respectively. The adults' baseline assessments, via the 46‐item Haem‐A‐QoL Questionnaire, and change over time at the 6‐month assessment were used in the psychometric analyses. Results: Internal consistency reliability was adequate (Cronbach's alpha > 0.70) for nine of the 10 Haem‐A‐QoL domains and for 'Total Score' in both trials at baseline (A‐LONG, n = 133; B‐LONG, n = 73). At baseline, several Haem‐A‐QoL domains and 'Total Score' demonstrated known‐groups and convergent validity when compared with other trial measures, including the EQ‐5D (items and total scores) and joint impairment. Change score correlations (baseline to 28 weeks) between the EQ‐5D and the Haem‐A‐QoL 'Total Score', and 'Physical Health' and 'Feelings' domains were moderate in magnitude (│ r │ ≥ 0.33; P < 0.03), demonstrating sensitivity to change for these outcome measures in A‐LONG. Conclusion: These psychometric analyses provide evidence of the reliability, validity and ability to detect change of the Haem‐A‐QoL to assess the HRQoL of adult males with severe haemophilia A and B in longitudinal clinical trials.